2018 Vegetable Production Handbook Chapter 5: Asian Vegetable Production - Guodong Liu; Christian F. Miller; Bonnie Wells; Yuncong Li; Qingren Wang (EDIS)
This 1-page fact sheet is chapter 5 of the 2018 Vegetable Production Handbook. Written by Guodong Liu, Christian F. Miller, Bonnie Wells, Yuncong Li, and Qingren Wang, and published by the Horticultural Sciences Department, 2018.